Etude des caractéristiques nutritionnelles et biométriques d’un poisson Pleuronectiforme : Citharus Linguatula (Linnaeus, 1758), pêché sur la côte de Mostaganem. - Boumediene, Ahmed Zin-eddine (My University, 2023)
This first work made it possible to provide information on some biometric parameters and the nutritional characteristics of Citharus Linguatula captured in the bay of Mostaganem. The study is based on a set of 40 individuals, 26 are females and 14 are males; sampled in Mostaganem bay for 4 months between December 2022 and March 2023. The sex ratio shows the dominance of females at 65%. The calculated relationships highlight a lower allometry between the total length and the standard length (Ls) and an upper allometry between the total length and the weight. This expresses that the total length (Lt) increases less quickly than the standard length (Ls) and that the weight (Wt) increases faster than the total length (Lt). The nutritional characteristics of Citharus Linguatula were determined by several methods such as the Soxhlet method for the determination of the lipid content and the Lowry method for the protein content, the results found inform us that the dab is a lean fish with 0.63 % lipid content, 18,48 % protein content, 20.5% dry matter content and 79.45% moisture content.
Keywords: Citharus Linguatula; biometrics; Mostaganem bay; Nutritional characteristics